Intercultural competence : interpersonal communication across cultures. - Koester, Jolene, ....-; Lustig, Myron W., ....- (Boston : Allyn and Bacon, 2010)
Presenting balanced coverage of skills and theory, Intercultural Competence provides students with the knowledgeable background and necessary skills to succeed in today's multicultural environment. Blending both the practical and theoretical, this thoroughly researched text offers students an enjoyable read and contemporary coverage of the impact of technology on intercultural communication and cutting-edge interpersonal scholarship. Intercultural Competence provides a discussion of important ethical and social issues relating to intercultural communication and encourages students to apply theory through vivid examples to prepare them to interact better in intercultural relationships.
Keywords: Interculturele communicatie